Using Google Forms as an Online Learning Assessment Tool for Non-EFL Students - Fitria, Tira Nur (Journal of English Language Teaching, Linguistics, and Literature Studies, 2023)
This research investigates the use of Google Forms as an online learning assessmenttool for non-EFL students at Institute Technology Business AAS Indonesia and toknow the strengths and limitations of Google Forms in assessing English students’learning. This is descriptive qualitative research. The method of collecting data in thisresearch used observation. The analysis shows that Google Forms is a practical,effective, and easy learning assessment tool for English lecturers in mid-term testsand final tests in English courses. We can use Google Forms by first logging into aGoogle account, making a learning assessment title, setting the initial learningassessment, deciding on question type, making questions, making answer keys anddefault scores, copying a URL link test, sharing, scoring, and analyzing the result. Wecan set a time limit for taking questions/quizzes on Google Forms so students canwork on test questions on time. Google Forms offers benefits that help us to createEnglish tests. It is free to use, easy to use, integrated with Google Sheets, can beeasily used and shared, and data presentation from respondents can be presented invarious forms, open source, saving cost, saving time and energy, storing datasecurely, integrated add-ons, having short URLs, having many choices of quiz menus,having auto-summary and real-time survey results. However, Google Forms haslimitations including limited design and font choices, limited export options only toGoogle Sheets and PDF, no email notifications, no editing/modification history, andGoogle Forms cannot be used in online discussion forums. However, the pros anddownsides of using Google Forms as an online assessment tool were not discussedin depth by the researchers. In this scenario, the researcher intends to carry out astudy on Google Forms by enrolling in the teaching site's 'English 2' course.Keywords: assessment tool, Google Form, online learning assessment